ANALISIS PENEGAKAN HUKUM TERHADAP PELANGGARAN LALU LINTAS OLEH ANAK DIBAWAH UMUR (STUDI PELAJAR SMP NEGERI 7 MUARO JAMBI BERDASARKAN PASAL 77 AYAT 1 UU NO. 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN) - Revalina, Atiqah; Irwan; Tohap Pandapotan Simaremare (Civic Education Perspective Journal, 2022)
The formulation of the problem in this study are: 1) What are the factors of traffic violations committed by minors; 2) How are law enforcement efforts against traffic violations by minors; 3) What are the inhibiting factors in law enforcement against traffic violations by minors. This study aims to determine law enforcement against traffic violations by minors studying at SMP Negeri 7 Muaro Jambi based on Article 77 Paragraph 1 of Law no. 22 of 2009 concerning Road Traffic and Transportation. This study uses a descriptive qualitative approach. The results of this study concluded that there are factors that influence minors to commit traffic violations, namely internal and external factors. Law enforcement against traffic violations by minors is carried out with efforts in the form of policies, whether carried out in the form of a sympathetic warning or given sanctions, namely ticketing. And there are two countermeasures if there are traffic violations by minors, the first is preventive to prevent and repressive efforts to improve such as giving warnings and ticketing. Barriers to law enforcement against traffic violations by minors are law enforcement factors, public awareness factors and the lack of thorough socialization of law enforcers.